Quality of Primary Care Services: a Perspective from Chronic Disease Patients - Jindan ZHANG, Xiaofan CHEN, Xiuhua MAO, Chenxi WANG, Xinting LIANG, Lu ZHANG, Aiyun CHEN (Zhongguo quanke yixue, 2022)
Background Since the number of chronic disease patients is increasing, relevant prevention and treatment services have become important long-term tasks for primary care institutions. However, problems in the provision of primary care services seriously affect the perception of such services in residents, especially chronic disease patients. Objective To understand chronic disease patients' assessment of the quality of primary care services, providing evidence for improving the quality of chronic disease management services in primary care. Methods A survey was conducted between July and August, 2020 with chronic disease patients (n=630) selected from primary care settings in Guangdong's Chaozhou by use of multistage stratified random sampling. The Primary Care Assessment Tool-Adult Simplified Version (PCAT-AS) (consists of 10 domains, including first contact accessibility, coordination, ongoing, comprehensiveness, community orientation and other 5 domains) was used in the survey for understanding chronic disease patients' assessment of the quality of primary care services. Multiple linear regression was adopted to identify factors potentially associated with the PCAT-AS score. Results Altogether, 553 cases (87.8%) who returned responsive questionnaires were enrolled for analysis. The average total PCAT-AS score for all respondents was (95.88±13.44) . The top three domains ranked in terms of average standardized score were comprehensiveness (services needed) (7.89) , first contact accessibility (7.72) , and first contact utilization (7.58) , and the bottom three-ranked domains were coordination (referrals) (5.61) , community orientation (6.11) and patient and family centeredness (6.40) . Multiple linear regression analysis indicated that higher total PCAT-AS score was associated with living in urban areas in contrast to rural areas〔b (95%CI) =-6.983 (-10.598, -3.368) 〕, senior high school and higher education level instead of junior high school and lower education level〔b (95%CI) =4.046 (0.966, 7.125) 〕, permanent residents without the local hukou in contrast to those with local hukou〔b (95%CI) =-5.360 (-9.517, -1.202) 〕, good self-rated health instead of relatively poor self-rated health〔b (95%CI) =-4.962 (-8.438, -1.486) 〕 or poor self-rated health〔b (95%CI) =-7.787 (-12.789, -2.786) 〕, having a contracted family doctor instead of having no contracted family doctor〔b (95%CI) =4.686 (2.508, 6.865) 〕, first choosing a community health center for treating common diseases instead of a village clinic〔b (95%CI) =-5.865 (-9.951, -1.779) 〕 or a district/county-level hospital or tertiary hospital〔b (95%CI) =-6.061 (-11.330, -0.792) 〕, 4-6 primary care visits instead of 1-3 primary care visits〔b (95%CI) =5.876 (3.367, 8.384) or 7 or more primary care visits instead of 1-3 primary care visits〔b (95%CI) =9.045 (6.512, 11.579) 〕, and high satisfaction with primary care services instead of fair satisfaction〔b (95%CI) =-2.844 (-4.817, -0.870) 〕 or dissatisfaction〔b (95%CI) =-10.418 (-17.050, -3.786) 〕. Conclusion Overall, Chaozhou chronic disease patients reported a sound level of treatment experience in primary care. Specifically, they reported good primary care experience in three domains, including comprehensiveness, first contact accessibility and first contact utilization, but poor experience in community orientation, and coordination (including information systems and referrals) . However, urban patients reported better primary care experience than rural patients. So continued efforts are needed to strengthen primary care performance in rural areas.